Classification of aerial acrobatics in elite half-pipe snowboarding using body mounted inertial sensors (P237) - Harding, J. W.; Mackintosh, C.; Hahn, A.; James, D. (The Engineering of sport 7, Volume 2, 2008)
We have previously presented data indicating that the two most important objective performance variables in elite half-pipe snowboarding competition are air-time and degree of rotation. Furthermore, we have documented that air-time can be accurately quantified by signal processing of tri-axial accelerometer data obtained from body mounted inertial sensors. This paper adds to our initial findings by describing how body mounted inertial sensors (specifically tri-axial rate gyroscopes) and basic signal processing can be used to automatically classify aerial acrobatic manoeuvres into four rotational groups (180, 360, 540 or 720 degree rotations). Classification of aerial acrobatics is achieved using integration by summation. Angular velocity (? i, j, k ) quantified by tri-axial rate gyroscopes was integrated over time (t = 0.01s) to provide discrete angular displacements (? i, j, k ). Absolute angular displacements for each orthogonal axes (i, j, k) were then accumulated over the duration of an aerial acrobatic manoeuvre to provide the total angular displacement achieved in each axis over that time period. The total angular displacements associated with each orthogonal axes were then summed to calculate a composite rotational parameter called Air Angle (AA). We observed a statistically significant difference between AA across four half-pipe snowboarding acrobatic groups which involved increasing levels of rotational complexity (P < 0.001, n = 216). The signal processing technique documented in this paper provides sensitive automatic classification of aerial acrobatics into terminology used by the snowboarding community and subsequently has the potential to allow coaches and judges to focus on the more subjective and stylistic aspects of half-pipe snowboarding during either training or elite-level competition. https://www.researchgate.net/search.Search.html?query=Classification%20of%20Aerial%20Acrobatics%20in%20Elite%20Half-Pipe%20Snowboarding%20Using%20Body%20Mounted%20Inertial%20Sensors%20&type=publication